Liquid phase exfoliation of antimonene: systematic optimization, characterization and electrocatalytic properties. Issue 39 (25th September 2019) - Gibaja, Carlos; Assebban, Mhamed; Torres, Iñigo; Fickert, Michael; Sanchis-Gual, Roger; Brotons, Isaac; Paz, Wendel S.; Palacios, Juan José; Michel, Enrique G.; Abellán, Gonzalo; Zamora, Félix
Abstract : Antimonene, a novel group 15 two-dimensional material, is attracting great attention due to its outstanding physical and chemical properties. Abstract : Antimonene, a novel group 15 two-dimensional material, is attracting great attention due to its outstanding physical and chemical properties. Despite its thermodynamic stability, the pronounced covalent character of the interlayer interactions imposes severe limitations on its exfoliation into mono- and few-layer. Here, we develop a systematic study of liquid phase exfoliation (LPE) with the aim to optimize antimonene production in terms of concentration and dimensional anisotropy, investigating the most relevant experimental factors affecting the exfoliation: pre-processing of pristine antimony, solvent selection based on Hansen solubility parameters and ultrasound conditions. Moreover, exhaustive characterization by means of turbidimetry, XRD, Raman spectroscopy, XPS, AFM, SEM, XEDS and TEM has been carried out. Indeed, we achieved concentration values of ca. 0.368 g L −1 (∼yield of 37 wt%), up to ∼30 times higher compared to the highest value so far reported, with ca. 50% of the nanolayers with heights between 2 and 10 nm and lateral dimensions in the 40–300 nm range. Furthermore, it has been demonstrated that the yield of the process can be enhanced up to ∼90 wt% by recycling the sediment to perform a maximum of 7 cycles. Moreover, we have illustrated the usefulness of this approach by characterizing the electrochemical behaviour of antimonene as a catalyst for the hydrogen evolution reaction (HER). This study provides important insights into the LPE and electrochemical properties of antimonene, allowing its large-scale production and paving the way for its application in fields of utmost importance such as energy storage and conversion or catalysis.